Pelatihan wirausaha pengolahan rumput laut - Amal Aqmal; Fatmawati Fatmawati; Nur Hadijah Yunianti (Universitas Negeri Makassar, 2020)
The Partners of the Community Partnership Program (PKM) are seaweed farmer groups, namely the partner group (1) Malelaya, its leader Sampara, and the partner group (2) Bina Mandiri, chaired by Daeng Nyau, who has a desire to develop a seaweed processing business in the lawi lawi becomes a new product, so it can be an alternative business. The problem of partners is not having the knowledge and skills in seaweed processing that can be marketed in the form of fast food. Another problem is that the type of seaweed jens lawi-selling is very low and easily damaged, so that it requires another alternative to be used as additional income in the family in particular. The implementation methods are: lectures, demonstrations, discussions, questions and answers, and assistance. The results achieved are (1) Partners have knowledge in seaweed processing. (2) The partner has knowledge and skills in processing pestle pestle pestle. (3) Partners have skills in making seaweed meatballs. (4) Mitra has various types of seaweed meatballs entrepreneurial spirit.